2008
DOI: 10.1136/ard.2008.088351
|View full text |Cite
|
Sign up to set email alerts
|

EULAR recommendations for the management of large vessel vasculitis

Abstract: Objectives: To develop European League Against Rheumatism (EULAR) recommendations for the management of large vessel vasculitis. Methods: An expert group (10 rheumatologists, 3 nephrologists, 2 immunolgists, 2 internists representing 8 European countries and the USA, a clinical epidemiologist and a representative from a drug regulatory agency) identified 10 topics for a systematic literature search through a modified Delphi technique. In accordance with standardised EULAR operating procedures, recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
395
1
41

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(439 citation statements)
references
References 84 publications
2
395
1
41
Order By: Relevance
“…5 EULAR recommends the starting dose of glucocorticoids 1mg/kg body weight for four weeks and then to taper them off. 5 We followed the same protocol in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 EULAR recommends the starting dose of glucocorticoids 1mg/kg body weight for four weeks and then to taper them off. 5 We followed the same protocol in our case.…”
Section: Discussionmentioning
confidence: 99%
“…4 Whereas, steroids with tapering doses are the mainstay of medical treatment; the refractory cases require additional therapy. 5 Reconstructive vascular surgery is limited to the severe and irreversible stenotic lesions. 3 Here we describe the course and management of pregnancy in a woman with Takayasu's arteritis.…”
Section: Introductionmentioning
confidence: 99%
“…2 The European League Against Rheumatism guidelines for the management of GCA recommend a temporal artery biopsy in all patients whenever a diagnosis is suspected (level of evidence 3, strength of recommendation C). 5 Nevertheless, Brack et al reported negative temporal artery biopsy in 42% of patients with large-vessel GCA. 6 Assie et al also observed a lower rate of positive temporal artery biopsy in patients with temporal artery GCA compared to those with involvement of upper and lower limb arteries (69% vs. 95%).…”
Section: Discussionmentioning
confidence: 99%
“…The recent British Society for Rheumatology (BSR) and British Health Professionals in Rheumatology (BSR and BHPR) guidelines for GCA management and EULAR recommendations for the management of large vessel vasculitides provide a thorough description of available induction and maintenance treatment options [121,122]. Initial treatment consists of high oral dose steroids, which must be slowly tapered over months (grade 3C).…”
Section: Giant Cell Arteritismentioning
confidence: 99%
“…Takayasu arteritis is usually treated similarly to GCA, with high-oral dose steroids (1 mg/kg/day), followed by slow tapering and steroid-sparing agents, such as MTX, AZA, and cyclophosphamide (grade 3C) [122]. An open-label study and a retrospective review, along with some case reports and series, have shown promising results of anti-TNF treatment, but randomized trials are still lacking [126,127].…”
Section: Takayasu Arteritismentioning
confidence: 99%